Pattern of acquisition of rotavirus antibody in children followed up from birth to the age of three years - Alexandre C. Linhares; Valéria R. Melo; Joana D'Arc P. Mascarenhas; Yvone B. Gabbay; Ronaldo B. de Freitas (Revista da Sociedade Brasileira de Medicina Tropical, 1989)
Nine hundred and forty-eight serum samples from 83 children living in Belem, Brazil, collected'within their first three years of life, were testedfor the presence of group- specific rotavirus-antibody by an enzyme-linked immunosorbent assay (ELISA) blocking-test. Passively transferred maternal antibody lasted about two and half months; subsequentely, low levels of rotavirus antibody started to appear at seven months, reaching a peak at eleven months of age. From one year onwards positivity gradually increased, reaching highest values at 34 months of life. Individual responses were examined in sera from 61 children who were followed up since birth to three years of age: 38 (62,3%) ofthem developed a long-term immunity following first infection; eleven (18.0%) children developed a short-term immunity after first infection by rotavirus; seven (11.5%) had no antibody response within their first three years of life; and 5 (8.2%) showed positive antibody response from birth to three years old.